A Study on Use of ICT in Online Admission Process in Higher Educational Institutions in Chhattisgarh - Dubey, P; Pandey, DK (International Journal of Computer Sciences and Engineering, 2025)
The present study attempts to find the impact of issues related to online admission on satisfaction in higher educational institutions Bilaspur. A proposed model covering eight different dimensions namely student satisfaction, transparency and efficiency, information access, ease of use, safety and security, resource utilization and value for money was tested in the study. The participants were the enrolled students of first year group of higher educational institutions who were practicing online system of admission. With the help of 100 participants data were collected and analyzed. Structural equation modeling with the help of AMOS was done to find the result and model fit. The outcome revealed that student satisfaction, transparency and efficiency, information access, ease of use, resource utilization, safety and security and value for money directly and positively affected the students satisfaction. The proposed model was found to be a good fit